Experimental investigation of non-premixed and partially premixed methane lifted flames established on a lobed swirl injector. (June 2021) - Jiang, Lei; Li, Gang; Jiang, Xi; Hu, Hongbin; Xiao, Bo; Xu, Yanji; Lei, Zhijun
A lobed swirl injector was tested to examine its potential in combustion control for non-premixed and partially premixed flames. It was found in the experiment that the flame derived from the injector changed between attached and detached flames at different conditions, demonstrating a promising way to control combustion. When air is supplied through the external channel of the lobed swirl injector and fuel passes through the internal channel, a stable lifted flame that is partially premixed was established above the injector exit. With the increase of airflow rate, the flame lift-off height decreases gradually until it is reattached to the injector, forming a diffusion flame. When increasing the fuel flow rate, the lift-off height increases gradually until the flame is blown out. Flow fields of the partially premixed lifted flames were investigated using stereoscopic particle image velocimetry. Streamlines located in the near field of the injector exit do not expand but bend inward, which is quite different from the expansion motion at the exit of the traditional vane swirler. The trough structure on the lobed swirler leads to the outer air flowing inward. Although the crest structure should make the inside gas flow outward, the strong entrainment of the surrounding air would restrain the radial outward motion of the inner gas, thus causing a contracted motion. After the streamline develops to an axial position further away from the injector exit, the swirling jet begins to expand under effects of both the centrifugal force and the development of shear layer to form turbulence. This flow pattern affects both the flame stabilization position and the neighboring reaction zone structure significantly. The measurements also show that the lobed swirl injector is very capable of entraining the ambient air that is sucked into the mainstream from the downward direction.